Immune Algorithm for Solving the Dynamic Economic Dispatch Problem - Aragón, Victoria S. (2016)
In this paper, an algorithm inspired on the immune system is presented, IA DED stands for Immune Algorithm Dynamic Economic Dispatch, it is used to solve the Dynamic Economic Dispatch problem. IA DED uses as differentiation process a redistribution power operator and the output power are integer values. The proposed approach is val- idated using three problems taken from the specialized literature. Our results are compared with respect to those obtained by several other approaches.